Potential application of high voltage electrical discharge plasma control of Brettanomyces bruxellensis in wine - Tomašević, Marina, enologinja (Array, 2019)
The aim of this work was to investigate the effect of high voltage electrical discharge (HVED) plasma on inactivation of Brettanomyces bruxellensis yeast in red wine. Research was conducted in two phases. Firstly, the efficacy of two main plasma parameters was examined - frequency (60, 90 and 120 Hz) and treatment duration (3, 5, 10, 20 and 30 min). Second phase included monitoring long-term effect of HVED plasma using optimal frequency during selected treatment durations, where culturability of B. bruxellensis was determined after 30, 60 and 90 days of storage. Results show that frequency of 120 Hz caused slightly higher inactivation than the lower ones. Furthermore, longer treatment durations resulted in significantly higher inactivation, wherein the treatment of 30 min showed the best results. Finally, during storage period, the inactivation effect of HVED plasma was reversed and B. bruxellensis yeast recovered almost completely in treated wine.